Microstructures and mechanical properties of friction stir dissimilar AA2024-O/AA6061-T6 welded joints at varying tool rotational speeds - Diana Puspita Sumarno; Mochammad Noer Ilman (Universitas Muhammadiyah Magelang, 2025)
Friction Stir Welding (FSW) is an innovative solid-state welding technique, especially for joints of unweldable metals or even dissimilar metals. In this study, FSW processes of two dissimilar metals, namely AA2024-O and AA6061-T6, were done at different tool rotational speeds of 910, 1500, and 2280 rpm whilst the welding speed was kept constant at 30 mm/min. This research was intended to improve the mechanical properties of the dissimilar FSW joints. A cylindrical pin-equipped tool was selected, and it was tilted at an angle of 2o during welding. Afterwards, microstructural observations, microhardness, and tensile tests were done. Results demonstrated that increasing tool rotation increased the peak temperature, accompanied by better mixing of different metals in the weld nugget zone (WNZ), hence resulting in improved microstructural homogeneity. The hardness distributions for all dissimilar FSW joints were characterized by the appearance of a high hardness region in the central part of WNZ, resulting in a peak of hardness. It was obtained that the FSW joint at 1500 rpm revealed the best ultimate tensile strength (UTS) around 170.38 MPa, which could be a result of precipitation hardening combined with a better homogeneity in WNZ.